Assessing learner satisfaction by simultaneously measuring learner attitude, motivation, loyalty and service quality in English academies. Issue 4 (4th July 2017) - Huong, Vu Thi; Casadesus, Marti; Marimon, Frederic
Abstract: The aims of this study are threefold in their approach to English academy teaching: (i) to assess learner satisfaction, (ii) to assess the impact of satisfaction on loyalty and (iii) to assess the three constructs that we considered to be the antecedents of learner satisfaction: learner motivation, learner attitude and service quality. To collect the data, a questionnaire was developed and delivered to 334 English learners in Spain in 2014. We concluded from these results that learner satisfaction is directly influenced by service quality; whereas learner motivation and learner attitude have no significant impact on learner satisfaction. Moreover, learner satisfaction has a strong impact on learner loyalty. The results also indicated that intrinsic motivation has a direct positive correlation with learner attitude and service quality, whilst extrinsic motivation has an insignificant relationship with learner attitude and a negative relationship with service quality. Amongst the four dimensions used to measure service quality two factors – namely teachers and tangibles (materials, equipment and facilities) – are the most important.